Community Initiative and Harmonizing: Key Strategies in Community-Based Tourism Development in Bejiharjo, Gunungkidul - Marlina, Endy; Wahyuhana, Ratika Tulus; Sukmawati, Annisa Mu’awanah (Humaniora, 2025)
This study examines the key strategies behind the success of community-based tourism in Bejiharjo Village, Gunung Kidul, Yogyakarta which has become a model of good practice compared to other less successful initiatives. Using a phenomenological approach, this study draws on two years of the researchers’ involvement in a local tourism development program. Through in-depth interviews and sustained engagement between 2022-2024, the research explores how the community articulated its aspirations and developped tourism strategies from the ground up. Findings shows that community initiative plays a critical role in encouraging the community to take ownership and lead tourism development. This challanges the assumption that community empowerment must be externally driven and highlights how meaningful local participation can lead to more sustainable and socially grounded outcomes. The study identifies six key strategies of community empowerment: (1) initiating, (2) networking, (3) mobilizing, (4) building trust, (5) protecting, and (6) harmonizing (integrating efforts for long-term sustainability). These findings provide insights for the government and stakeholders in tourism development to plan better programs resulting in more benefits for improving community welfare.